COMPARISON OF INTUBATION QUALITY AND HAEMODYNAMIC RESPONSE IN ENDOTRACHEAL INTUBATION BETWEEN SUPERIOR LARINGEUS AND TRANSTRACHEAL BLOCK AND MUSCLE RELAXANTS - Primadita, Hanggia; Murti, Bhisma; Santosa, Sugeng Budi (Malang Neurology Journal, 2018)
Background. Endotracheal intubation stimulates various responses such as coughing and bucking, bronchial and laryngeal spasm and hemodynamic changes. Muscle relaxants facilitate easy intubation, but not suppressing hemodynamic response. Superior laryngeus and transtracheal block is presume to suppress hemodynamic changes while maintain intubation quality.Objective. To compare intubation quality and hemodynamic response from superior laryngeus and transtracheal block and muscle relaxants.Methods. Intubation quality is assessed using Helbo-Hansen Raulo and Trap Anderson. Blood Pressure, pulse and saturation were measured before and after intubation.Results. All intubation is acceptable in muscle relaxants group (100%), one unacceptable in block group (5.9%). After intubation hemodynamic in both groups were significantly different (p=<0.05) for systolics (148.35±26.33 vs 109.53±15.98), diastolics (94.88±20.18 vs 68.00±15.54), MAP (109.65±21.18 vs 79.94±16.94), and for pulse (101.71±16.34 vs 87.47±20.03), except for saturation (99.35±0.79 vs 99.35±0.99).Conclusion. Muscle relaxant and block deliver similar intubation quality, however block giving out better hemodynamic response stability.